Mapping the tidally disrupting Andromeda XXVII and its stellar stream. Issue Volume 11:Issue S321(2015) (21st March 2017) - Preston, Janet; Collins, Michelle; Bonaca, Ana; Ibata, Rodrigo; Tollerud, Erik; Geha, Marla; ,
Abstract: Andromeda XXVII is a dwarf spheroidal galaxy in the outskirts of the Andromeda galaxy (M31). It appears to be dissolving in to the Northern arc of M31, and could be the remnant of a strong tidal disruption. In the upcoming months, our spectroscopic program, which has measured velocities for multiple stars within both the dwarf galaxy progenitor and its stream (using the Keck II DEIMOS telescope, as part of the PAndAS survey), will determine velocity dispersions, scale radii and metallicities of both the dwarf and the stream. This in turn may enable us to ascertain the progenitor mass profile and determine whether it is cusped or cored.